E-Commerce in India- A New Perspective - Pankaj Gupta; Ankur Sharma (Integrated Journal for Research in Arts and Humanities, 2022)
As an advancement in technologies based on Web and Internet, the differences between traditional marketplaces and the world’s e-commerce market—such as corporate capital size, are becoming meaningless. The strategic positioning or a company's ability to identify emerging opportunities and apply the required human skills (such as intellectual resources) to grab them through an e-business strategy that is simple, workable, and practical in today’s business environment and global information scenario and contribute to a new economic environment. E-commerce, when combined with the appropriate strategy and policy approach, allows small and medium-sized firms to compete with large and capital-rich corporations by levelling the playing field. On a different level, emerging countries are allowed wider reach to world’s economy, where they can fight competition with more established economies. Almost all developing countries, if not all, are already involved in electronic commerce, either as manufacturers/sellers or purchasers/customers. However, these countries are having comparatively poor information infrastructure which must be strengthened in order to support e-commerce growth. The following are some of the policy areas where action is needed: Limited credit card availability and a common nationwide credit card system; High cost of Internet access which includes service fees, communication fees, and hosting charges; Poor transportation infrastructure leads to slow and uncertain delivery System; Lack of advance technologies (i.e., an insufficient professional IT workforce) and poor skilled human resources and; Content restrictions based on some public policy and national security, which have a significant impact on businesses in the information services sector, such as the entertainment industries and media; Network security issues and insufficient security safeguards. In this research paper we will try to find out the current scenario of electronic-commerce in India and also look upon the opportunities and challenges in e-commerce in India.